Korean Language Teaching Methods in Tarumajaya Village, Kertasari - Indrati Asyariri; Adhitya M. Maheswara; Syifa Fatimazzahroh; Lia Amelia Nurkhazanah (SWAGATI : Journal of Community Service, 2026)
In the era of globalization, language has become one of the essential competencies that must be mastered due to its significant role in the communication process. Therefore, language teaching at every level of education has become increasingly important. The teaching methods employed by language teachers and instructors are also expected to adapt to the development of the times and advancements in technology. However, several regions, particularly rural areas, still face limitations in terms of access and facilities needed to implement digitally oriented teaching methods. In this regard, training on language teaching methods can be regarded as an urgent necessity to be conducted in Tarumajaya Village, Kertasari. The team of lecturers from Universitas Siber Asia proposes this training program with the expectation of improving the competencies of language teachers and instructors in the village.